HUBUNGAN PENGETAHUAN TERHADAP PERILAKU PENGGUNAAN SUPLEMEN DAN OBAT HERBAL DALAM MENCEGAH PENULARAN COVID-19 DI BANJARBARU SELATAN - Esty Restiana Rusida; Syahrizal Ramadhani; Depy Oktapian Akbar (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Indonesia is one of the highest confirmed countries in ASEAN and South Kalimantan is still in the 13th order category in Covid-19 cases. One of the measures to prevent its spread is to increase the immune system by consuming health supplements or herbal medicines. Knowledge influences in shaping one's behavior. The purpose of this study was to determine the relationship between knowledge and behavior in the use of supplements and herbal medicines in preventing the spread of Covid-19 in South Banjarbaru. This research is descriptive analytic with a cross sectional design, data collection by proportional random sampling technique with an instrument in the form of google form with a sample of 398 respondents. The data analysis used is univariate and bivariate using chi square. The conclusion shows that the level of public knowledge about supplements and herbal medicines in the South Banjarbaru sub-district is mostly knowledgeable enough by 43.5% with the majority of the behavior of using supplements and herbal medicines being inappropriate at 68.3%. The results of the chi square statistical test showed that there was a relationship between knowledge and behavior in the use of supplements and herbal medicines with a value of 0.000 (sig. <0.05).